Efficacy and safety of Brucea javanica oil emulsion for liver cancer: A protocol for systematic review and meta-analysis. Issue 47 (20th November 2020) - Luo, Didi; Hou, Daorui; Wen, Tiancheng; Feng, Meiling; Zhang, Haiming
Abstract: Background: Brucea javanica oil emulsion (BJOE), extracted from the Chinese herb Bruceae Fructus (Yadanzi), is a broad-spectrum anti-tumor drug and has been widely used for the treatment of liver cancer in China. The aim of this study is to systematically investigate the efficacy and safety of BJOE for the treatment of liver cancer. Methods: Seven electronic databases including the Cochrane Library, PubMed, Excerpt Medica Database, Chinese Biomedical Literature Database, China National Knowledge Infrastructure, China Scientific Journal Database, and Wanfang Database will be systematically retrieved for data extraction from their inceptions to September 2020. Cochrane Risk of Bias tool will be used to assess the risk of bias of included studies. The RevMan 5.4 and Stata 16.0 software will be applied for statistical analyses. Statistical heterogeneity will be computed by I 2 tests. Sensitivity analysis will be conducted to evaluate the stability of the results. The publication bias will be evaluated by funnel plots and Egger test. The quality of evidence will be assessed by the GRADE system. Results: The results of our research will be published in a peer-reviewed journal or presenting the findings at a relevant conference. Conclusion: The conclusion of this study will provide helpful evidence of the effect and safety of BJOE for the treatment of liver cancer in clinical practice. OSF registration number: 10.17605/OSF.IO/UC8XQ